Reformulating the Legal and Institutional Mandate of BNPB in Disaster Mitigation Policy - Ellectrananda Anugerah Ash-shidiqqi; Rindia Fanny Kusumaningtyas; Mutiara Dwi Sari (Indonesian Journal of Administrative Law and Local Government, 2025)
Disaster mitigation in Indonesia requires a coherent and adaptive institutional framework capable of addressing the country’s high vulnerability to natural hazards. The National Disaster Management Agency (BNPB), as the central authority for disaster management, faces persistent challenges in coordination, regulatory fragmentation, and institutional rigidity that undermine its capacity for effective mitigation. This article examines the need to reconstruct the legal and institutional architecture of BNPB to strengthen its preventive and risk reduction functions. Using a qualitative juridical-normative approach combined with policy analysis, the study explores the alignment between existing disaster laws, decentralization policies, and international disaster governance standards such as the Sendai Framework for Disaster Risk Reduction. The findings reveal that BNPB’s current legal mandate remains overly response-oriented, lacking clear authority and integration mechanisms with regional disaster agencies (BPBD) and sectoral institutions. Therefore, the paper proposes a reconstruction model emphasizing legal harmonization, institutional redesign, and collaborative governance among central and local actors. Such a transformation is expected to shift BNPB’s paradigm from reactive disaster response toward proactive, community-based, and sustainable disaster mitigation—anchored in legal certainty, institutional accountability, and resilience-oriented policy coherence.